Role of Starter Cultures on the Safety of Fermented Meat Products - Laranjo, Marta; Potes, Maria Eduarda; Elias, Miguel (Frontiers in Microbiology, 2019)
Starters are microbial cultures used to promote and conduct the fermentation of meat products. Bacteria, particularly lactic acid bacteria (LAB) and coagulase-negative staphylococci, as well as yeasts and moulds, may be used as starters. They can increase the safety of fermented meat products by means of rapid matrix acidification or due to the production of antimicrobial substances, such as bacteriocins. Besides, starters may help to standardise product properties and shorten ripening times. Safety of fermented meat products may be jeopardised by microbiological, namely foodborne pathogens (Salmonella spp., Listeria spp., etc), and chemical hazards, particularly biogenic amines, nitrosamines, polycyclic aromatic hydrocarbons, and mycotoxins. Biogenic amines (BA) are potentially unsafe nitrogenous compounds that result from the decarboxylation of some amino acids. Some microorganisms may be responsible for their formation. Starters can cause a fast pH decrease, inhibiting the development of microorganisms with amino acid decarboxylative ability, thus preventing the accumulation of BA in fermented meat products. Besides, starters can compete with the autochthonous, nonstarter microbiota throughout ripening and storage, thus reducing BA production. Some strains of Lactobacillus sakei and Lactobacillus plantarum have been shown to reduce the formation/accumulation of BA. On the other hand, Staphylococcus xylosus and Debaryomyces hansenii strains have been reported to degrade biogenic amines in food. Polycyclic aromatic hydrocarbons (PAH) are organic compounds containing multiple aromatic rings and produced by the incomplete combustion of organic matter, such as the wood used for smoking meat. Mixed starters containing Lactobacillus spp., Gram-positive catalase-positive cocci and yeasts have been used in the manufacturing of traditional meat sausages. However, the effect of starters on reducing the accumulation of PAH is poorly understood. Starters may also be engaged in competitive exclusion, outcompeting the spoiling or deteriorating autochthonous microbiota. For example, Pediococcus acidilactici has been shown to inhibit Listeria monocytogenes in meat products. Additionally, the role of moulds, such as Penicillium nalgiovense, in the competitive exclusion of undesired filamentous fungi, has also been demonstrated. Most of these undesired fungi produce mycotoxins, secondary metabolites capable of causing disease. The current review addresses the role of starters on the microbiological and chemical safety of fermented meat products.